Factors Influencing Adoption of Sustainable Supply Chain Management Practices Among Manufacturing Firms - Johnson NSOWAH; Maxwell Agabu PHIRI (International Journal of Environmental, Sustainability, and Social Science, 2023)
There is a significant gap in emerging nations such as Ghana on factors influencing the adoption of Sustainable Supply Chain Management (SSCM), as most of these studies are conducted in advanced nations. As a result, this study investigates the factors influencing manufacturing companies in Ghana's adoption of SSCM practices. Three hundred and three 303 manufacturing firms with an annual turnover of not less than one million dollars ($1,000,000) were purposively selected for the study. Throughout the study, close-ended questionnaires were adopted for the data collection. Structural equation model (SEM) was used to examine empirically the factors that influence the firms’ adoption of SSCM. The study revealed that adoption of SSCM is influenced by instrumental, moral, and knowledge factors. Based on the study outcomes presented and discussed, the study concluded that instrumental, relational, moral and knowledge factors affected the adoption of SSCM practices by firms in Ghana Further studies on the subject can adopt a case study approach, as this method will be able to investigate the topic in a manner that allows for a more in-depth comprehension of the subject in a particular context.